Alienation, neoliberalism and education - Niels Rosendal Jensen (Social Work & Society, 2019)
"Faster, higher, stronger" - these adjectives are not solely the motto of the Olympic Games but apparently of education policy in Denmark, too. It is 'evident' that fastness (or speed), capacity and competitiveness permeate the major part of educational thinking and become instruments in the struggle on market shares of the global competition. However, we are risking that we are getting more stupid as well. The intention of this article is to describe and understand alienation as experienced in education. The article does not offer a final and comprehensive analysis. The purpose is much more humble as the aim is to assess the explanatory power of a minor selection of theoretical work based on the concept alienation. In celebration of the bicentenary of Karl Marx, the first part departs from his concept of alienation and its four main aspects, namely: (1) man is alienated from nature; (2) he is alienated from himself (from his own activity); (3) from his "species-being" (from his being as a member of the human species) and (4) man is alienated from man (from other men). In addition, this part includes modern interpretations of alienation by drawing on Mészáros, Harvey, Rosa, Collins, De Lissovoy and Jaeggi aiming at establishing a broader analytical base. The second part of the article presents an analytical description of education policy in Denmark seen through the lenses of  the concept of alienation. The article is tracking how the modern system of education reproduces the aspects of alienation that in turn express the crisis of education (and the crisis of society).